Ways of Providing Competitive Sustainability of Trade-Food Companies - S. G. Vasin (Вестник Российского экономического университета имени Г. В. Плеханова)
Trends and ways of providing competitive sustainability of trade-food companies that are adequate to the current social and economic situation on the market make up the most acute goal of research aiming at their immediate implementation by business. Provision of competitive sustainability should touch upon all spheres of trade-food company work: from the product range, shaping and promoting the offer to rendering the required services and further servicing. This process is an integral part of the proposed new model to be implemented by participants of food market on the basis of principles relevant to today’s conditions. First of all it is building up of competitive behavior on market based on systemacity, reliability, flexibility; attraction of a great deal of customers based on service, feedback; increase in profits based on principles of optimization, efficiency; growth in the market share based on computerization, high automation of processes, integration, etc. And the key factor of success on food market is the ability of participants to increase market cover, customers, receipts and profits with cost cutting.  The article studies theoretical foundations of competitive sustainability of trade-food companies; analyzes competitiveness of food market of the Russian Federation; puts forward methods of providing competitive sustainability of trade-food companies.